Impact of the Human Development Index, Economic Growth, Investment, and Government Expenditure on the poverty of districts and cities in Bengkulu Province - Febria Wulandari; Roosemarina Anggraini Rambe (UNIVED Press, 2024)
The purpose of this research is to observe the influence of the human development index, economic growth, investment, and government spending on the poverty rate in districts and cities in Bengkulu Province. Data used as panel data for the period 2014–2020 The method of analysis used is panel data regression. Research results show that the human development index has a significant impact on poverty levels. Economic growth significantly affects the poverty level. Investment significantly influences the level of poverty. As well, government spending affects poverty rates in the Bengkulu City district.